Dam maintenance and rehabilitation II : proceedings of the 2nd International Congress on Dam Maintenance and Rehabilitation, Zaragoza, Spain, 23-25 November 2010 - International Congress on Dam Maintenance and Rehabilitation (2nd : 2010 : Zaragoza, Spain); Garcia, Rafael Romeo (London, ENK. : CRC, 2011)
Includes bibliographical references and index